The state of industrial traumatism and professional diseases in Ukraine - Berezovskyi , A. P.; Trus , O. M.; Prokopenko , Ye. V. (Scientific Progress & Innovations, 2019)
The purpose of the article is to investigate the state of industrial traumatism and professional diseases in Ukraine, to identify the causes of injuries and ways to prevent them. Methods of the research. We used the statistical method to determine the quantitative indicators characterizing the general level of industrial injuries (statements according to H-1 form) and professional diseases (statements according to П–4 form). The research results. The article presents the comparative analysis of the level of occupational injuries and professional diseases in the industries according to field of survey and the regions of Ukraine over the period from 2015 to 2017. It has been established that the indices of industrial injuries including fatal accidents show a declining tendency. In 2017 as compared with the same period in 2016, the number of injured employees at workplaces decreased by 115 persons or by 2.6 % (4313 injured as compared to 4428 respectively). In comparison with 2015, the level of workplace injuries in 2017 increased by 1.2 % or 53 persons (4313 injured as compared to 4260 correspondingly). There has been an increase in the injury rate at the enterprises of different branches, namely: in social-cultural sphere and trade, coal-mining industry, machine-building, construction, housing and utility sector. Workplace injury level increased in 2017 as compared to 2015 in Dnipropetrovsk, Zaporizhzhia regions and Kyiv. The level of fatal workplace injuries in Ukraine in 2017 decreased by 34 persons or 8.5 % (366 fatal casualties against 400) compared to 2016 and by 9 persons or 2.5 % (366 fatal accidents against 375) compares to 2015. In comparison to 2015, the level of fatal injuries in 2017 increased in the construction, transport, boiler maintenance, lifting devices. The highest level of fatal accidents at work places over the period of 2015–2017 was recorded in Dnipropetrovsk, Donetsk, Kyiv, Lviv, Kharkiv, Poltava, Odesa regions. In the structure of professional diseases those of the respiratory system rank first (779 cases). Muscular-skeletal disorders (590 cases) rank second, vibration disease takes the third place (143 cases) and hearing disorders are in the fourth place (107 cases). Other diseases in the structure of professional illnesses make up 8.5 %. It has been established that the greatest number of professional diseases was in the extractive industry and quarry development. The elements of scientific novelty. It has been established that the indicators of industrial injuries, including fatal, tend to decrease. There has been an increase in the number of occupational diseases at work as compared with the previous years. Practical importance. Social-cultural sphere and trade, coal-mining industry, agro-industrial complex, transport, machine-building, metallurgy, construction, chemical industry, and power engineering remain the most traumatic industries.